A Digitally Disruptive Supply Chain. (December 2015) - Ady, Jacklyn
Abstract : It's inevitable—the traditional supply chain will eventually meet the digital frontier. Imagine today's new community of makers sourcing designers to refine their inventions, and 3D printers to generate first‐round prototypes. What will this brave new world look like? The future of the supply chain in the digital age…